0297 THE EFFECT OF COGNITIVE-BEHAVIORAL THERAPYON INTRINSIC FUNCTIONAL CONNECTIVITY IN PATIENTS WITH PSYCHOPHYSIOLOGICAL INSOMNIA: A RESTING STATE FMRI STUDY. (28th April 2017) - Lee, YG; Kim, S; Kim, N; Choi, J; Park, J; Kim, S; Lee, Y
Abstract: Introduction: We evaluated the changes of intrinsic resting-state functional connectivity (FC) in response to cognitive behavioral therapy for insomnia (CBTi) in patients with psychophysiological insomnia (PI). Methods: Thirteen patients with PI (age 51.0 ± 10.2, 10 women) underwent resting-state functional MRI scans both before and after CBTi consisting of 5 sessions without medication for FC analysis with the frontostriatal regions as seed regions by the Harvard-Oxford Atlas. Self-reported sleep scales were evaluated before and after CBT-I, respectively. Sleep parameters were calculated according to sleep diaries recorded by the patients before and after CBTi, respectively. Scores of Beck Depression Inventory were adjusted in all of the analyses. Results: After CBTi, FC decreased between the prefrontal cortex and occipital cortex, precuneus, motor-somatosensory cortices but increased between the prefrontal cortex and posterior cingulate cortex. After CBTi, FC decreased between the medial frontal regions (anterior cingulate cortex, paracingulate cortex) and motor-somatosensory, lateral occipital cortices but increased between the left orbitofrontal cortex and both left putamen and pallidum. After CBTi, FC decreased between the right thalamus and right superior parietal cortex; left putamen and right superior frontal, left supplementary motor area whereas increased between the left caudate and left supramarginal cortex; the left hippocampus and left frontal pole, left supramarginal, right paracingulate cortices; the left accumbens and the left precentral, right occipital fusiform cortices. After CBTi, changes in measures of sleep parameters by sleep diaries and sleep scale scores significantly correlated with FC change between the frontoparietal cortex and subcortical regions including the striatum, thalamus, hippocampus, accumbens, and insular. Conclusion: Frontostriatal network have been hypothesized to be a key pathway in the sleep-wake cycle. Current results suggest the frontostriatal network to be involved in the neurobiological mechanisms of CBTi by regulating hyperarousals, emotional and cognitive processing. Support (If Any): This research was supported by Basic Science Research Program through the National Research Foundation of Korea funded by the Ministry of Education (Study No.: 2013R1A1A2062517, Dr. Yu Jin Lee) and the Brain Research Program through the National Research Foundation of Korea funded by the Ministry of Science, ICT & Future Planning(Study No.: NRF-2016M3C7A1904336, Dr. Seog Ju Kim).